Meningkatkan Kompetensi Guru Dalam Menerapkan Strategi Pembelajaran Abad 21 Melalui Workshop Edukasi Guru Di Desa Banyuresmi - Fanny Nurani; Winda Sari Rahayu; Vina Noviana Hadiansyah; Zufani Jannah Hamidah; Nur Alam Ulumuddin Zuhri (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The increasingly rapid development of the times demands changes in the world of education, including in terms of implementing learning strategies. In Banyuresmi Village, there are still many teachers who have not fully mastered 21st century learning strategies. This is the background for carrying out this community service. The aim of this service is to increase teacher competence in implementing 21st century learning strategies so that they can improve the quality of student learning. The method used in this service is through teacher education workshops which include material on 21st century learning concepts, various kinds of learning strategies that can be applied, as well as direct practice in designing learning activities. The workshop participants were all teachers in Banyuresmi Village. The results of this service show a significant increase in teacher competence in implementing 21st century learning strategies. This can be seen from the increase in teachers' understanding of 21st century learning concepts and their ability to design innovative learning activities. Apart from that, based on the evaluation results, teachers also responded positively to the implementation of the workshop and showed high interest in implementing new strategies in classroom learning. It is hoped that this workshop can be the first step in efforts to improve the quality of education in Banyuresmi Village.